Prediction of in vitro and in vivo DM digestibility of different forages using rumen liquor and dung liquor as inoculum - Kumar, Shiv; Gupta, P C (The Indian Journal of Animal Sciences, 2012)
Samples (24) of known digestibility were taken for in vitro dry-matter digestibility using rumen liquor (RL) and dung liquor (DL) as source of inoculum. The in vitro dry-matter digestibility coefficients obtained by using RL and DL were positively correlated (P